Effects of microplastics on microbial community and greenhouse gas emission in soil: A critical review - Guanlin Chen; Saisai Guo; Linan Liu; Wenzhu Zhang; Jingchun Tang (Ecotoxicology and Environmental Safety)
Microplastics (MPs) are ubiquitous in soil ecosystems and significantly impact soil microorganisms and greenhouse gas (GHG) emissions. Although some reviews have summarized their impact on greenhouse gas emissions, no systematic analysis has been conducted on how soil physicochemical and microbial properties affect these emissions. Firstly, this review details that MPs alter microbial abundance, structure, activity and gene expression, directly stimulating CO2 and N2O emissions, though their impact on CH4 remains inconclusive. Additionally, MPs change rhizosphere microbial growth, cause soil nutrient loss, and induce plant toxicity, indirectly affecting GHG emissions. Finally, this article suggests strengthening research on rhizosphere and MPs surface microbial communities, exploring interactions with clay and minerals, and investigating GHG emission mechanisms to understand the ecological effects of MPs.